Conversion of Percutaneous Cholecystostomy to Endoscopic Gallbladder Stenting by Using the Rendezvous Technique - Kwangwoo Nam; Jun-Ho Choi (Clinical Endoscopy, 2017)
We report the successful conversion of percutaneous cholecystostomy (PC) to endoscopic transpapillary gallbladder stenting (ETGS) with insertion of an antegrade guidewire into the duodenum. An 84-year-old man presented with severe acute cholecystitis and septic shock. He had significant comorbidities, and emergent PC was successfully performed. Subsequent ETGS was attempted but unsuccessful owing to difficulties with cystic duct cannulation. However, via the PC tract, the guidewire was passed antegradely into the duodenum, and ETGS with a double-pigtail plastic stent was successfully performed with the rendezvous technique. The PC tube was removed, and no recurrence was reported during the 17-month follow-up period. Conversion of PC to ETGS is a viable option in patients with acute cholecystitis who are not candidates for surgery. Antegrade guidewire insertion via the PC tract may increase the success rate of conversion and decrease the risk of procedure-related complications.